2021
DOI: 10.1115/1.4051306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Strain Transfer Behavior of Molybdenum Ditelluride (MoTe2) Thin Films

Abstract: Transition metal dichalcogenides (TMDs) offer superior properties over conventional materials in many areas such as in electronic devices. In recent years, TMDs have been shown to display a phase switching mechanism under the application of external mechanical strain, making them exciting candidates for phase change transistors. Molybdenum ditelluride (MoTe2) is one such material that has been engineered as a strain-based phase change transistor. In this work, we explore various aspects of the mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Molecular statics (MS) simulations were done using LAMMPS open source software. , The unstrained, DFT relaxed TBG moiré lattice was transformed into an orthogonal cell for performing MS simulations. The simulation box is considered with free surface boundary conditions in the direction of uniaxial strain, allowing us to account for the aperiodic crystal geometry (or moiré lattice mismatch) due to strain applied to one of the TBG layers.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular statics (MS) simulations were done using LAMMPS open source software. , The unstrained, DFT relaxed TBG moiré lattice was transformed into an orthogonal cell for performing MS simulations. The simulation box is considered with free surface boundary conditions in the direction of uniaxial strain, allowing us to account for the aperiodic crystal geometry (or moiré lattice mismatch) due to strain applied to one of the TBG layers.…”
Section: Methodsmentioning
confidence: 99%
“…[175,176] Other TMDCs, including MoSe 2 and MoTe 2 , displayed comparable mechanical properties, such as a high Young's modulus and strength. [177][178][179][180] Due to their diverse chemical compositions and structural phases, TMDCs exhibit a broad spectrum of electrical properties, ranging from metallic to semiconductor to insulator, as well as unique topological electronics phases. [159,[181][182][183][184] Specifically, the electronic properties of TMDCs are strongly dependent on the filling of the transition metal ions' nonbonding d orbitals: metallic behavior occurs when the nonbonding d orbitals are partially filled, while semiconducting behavior occurs when all nonbonding d orbitals are occupied.…”
Section: Transition Metal Dichalcogenide (Tmdc)mentioning
confidence: 99%
“…[ 175,176 ] Other TMDCs, including MoSe 2 and MoTe 2 , displayed comparable mechanical properties, such as a high Young's modulus and strength. [ 177–180 ]…”
Section: D Materials and Their Propertiesmentioning
confidence: 99%
“…Similarly, recent results have shown that depositing stressed thin films onto 2D materials can induce strain transfer into the 2D material itself (Figure 14b). 208,214,215 This technique relies on the fact that thin films typically have some amount of process induced stress from deposition, and this stress can relax by transferring strain into the 2D material. This has been shown to be controllable in magnitude by varying film stress as well as controllable in type (uniaxiality vs biaxiality) and directionality through lithographic patterning.…”
Section: Straintronics Based On 2d Materialsmentioning
confidence: 99%